Probing fretting behavior of Mg–Sn–Y alloy under high-performance fluids lubrication. (October 2019) - Huang, Zhenjie; Li, Wen; Fan, Xiaoqiang; Zeng, Ying; Cai, Zhenbing; Zhu, Minhao
Abstract: The attention is focused on high-performance Mg alloys due to their favorable biocompatibility, lightweight, physicochemical and mechanical properties. Here, the fretting performance of Mg–Sn–Y alloy was evaluated under fluids lubrication, and the fretting mechanism was explored in detail via analysis of wear track/debris using SEM and XPS depth profile. The results illustrate that the friction reduction is superior to wear resistance for lubricated Mg–Sn–Y/Steel contact under fretting conditions, mainly depending on the oil-film induced transformation of fretting running regime and transition of fretting wear (from adhesive/oxidation wear and delamination under dry friction to abrasive wear and delamination under fluids lubrication). Hence fretting performance of Mg–Sn–Y alloy under fluids lubrication depends on fretting running regime and synergy of oil-film/protective film. Graphical abstract: Image 1 Highlights: The fretting running regime and wear mechanism of Mg–Sn–Y alloy under lubrication conditions are first investigated in detail. The introduction of lubricants can transform the fretting running state of Mg–Sn–Y/Steel contact. Wear debris and transfer layer can enhance the mechanical properties of mating interfaces, change the fretting regime, and reduce friction and wear. XPS depth profile reveals the tribo-chemical reaction films composed of MgO, Mg(OH)2, MgCO3, MgF2 and Y2 O3 .